Clozapine-induced agranulocytosis - Luque Espino, Julio César (2020)
Clozapine currently remains the gold standard for treatment-resistant schizophrenia, but only under an adequate hematological monitoring, because it is associated with agranulocytosis. Clozapine is metabolized to produce pharmacologically active N-desmethylclozapine, inactive clozapine N-oxide and reactive oxygen species (nitrenium ion). A neutrophil count < 1000 cells/mm3 corresponds to a state of neutropenia. Agranulocytosis is a severe state of neutropenia with an absolute neutrophil count < 500 cells/mm3. Clozapine is associated with agranulocytosis in approximately 0.8 % of the patients, with an increased risk in older people and women. There are two mechanisms that explain the clozapine-induced agranulocytosis: immunological (response mediated by the immune system against haptenized neutrophils) and toxic (by the action of the metabolites N-desmethylclozapine and nitrenium ion). Pharmacogenetics represents a valuable tool to achieve the so-called personalized medicine by adapting and individualizing the treatment based on the genetic markers of each patient. Several studies have shown a potential association of clozapine-induced agranulocytosis with certain HLA haplotypes (HLA-B38, DR4, DQw3 and DQB1). After a patient has presented agranulocytosis, three mechanisms of clozapine rechallenge are known: simple, with lithium and with factors that stimulate granulocyte colonies. Due to the risk of agranulocytosis, clozapine formulations are available only through a controlled distribution, with a detailed record of the patients, and with a mandatory and systematized pharmacovigilance.